EXPLORING THE ASSOCIATION BETWEEN AUTOANTIBODY PROFILES AND THE DEVELOPMENT OF DIGITAL ULCERS IN SYSTEMIC SCLEROSIS PATIENTS: A COMPREHENSIVE ANALYSIS - Yamancan, G.; Karatas, A.; Erden, A.; Sari, A.; Babayigit, A.; Guler, A. Avanoglu; Koca, S. S. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Observational studies/registry; Autoantibodies